Value systems among adolescents: Novel method for assessing level of ego‐development. Issue 2 (April 2017) - Kjellström, Sofia; Sjölander, Per; Almers, Ellen; Mccall, Mary E.
Abstract : Children's value systems develop through youth and influence attitudes and actions. But there is a lack of appropriate measures for children and adolescents. The objective of this study was to construct and validate a questionnaire that reveals distinct value systems among adolescents, and to evaluate the identified value systems' relationship to degree of ego‐development and moral development. A quantitative study in a Swedish School with ages 12 through 16 (grades 6 to 9) was performed (N = 204). A set of pattern recognition statistical analyses has been used to identify different profiles of values systems and demonstrate that these systems can be arranged in a hierarchical order similar to other development. Results revealed three value systems in this sample. The identified value systems reflect different degrees of moral and ego‐development among children in the study. Three distinct value systems were identified: the first (n = 9) and the second value systems (n = 35) correspond to pre‐conventional stages, and the third value system (n = 155) corresponds to early conventional stages of ego development. Ego development scoring of test statements to assess stages. The value system was significantly related to moral development in the personal interest and the maintaining norms schemas of the Defining Issues Test (DIT). However, many students did not complete the entire DIT, so those results should be looked at with caution. It appears that this new test (Test for Adolescent Value Systems – TAVS) does relate to an established ego development rating scale.